An Analysis Students’ Difficulties in Reading Comprehension of Descriptive Text - Wilda Fitri; Eliza Eliza; Irwandi Irwandi; Loli Safitri (Journal of English Language and Education, 2022)
This study aims to explain the kind of difficult aspect in reading comprehension of the descriptive text faced by the students at eighth grade of SMPN 1 Sintoga. The method applied was descriptive quantitative, where the test and questionnaire were used as the instrument of the data. The sample of this study was VIII 2  chosen by using a simple random sampling technique. The test consisted of 30 question items divided into five types of questions: topic, main idea, word reference, location information, reference. Index difficulty and percentage were used to analyze the data. The result of the test showed that the majority of the eighth-grade students of SMPN 1 Sintoga found difficulties including answering topic 76%, main idea 72%, word reference 79%, location information 62%, and reference 80%. The kind of difficult aspect that encountered by the students of SMPN 1 Sintoga was finding main idea questions because the located main idea was difficult to find. As the result, kind of the difficult aspect faced by was in achieving the inference for reading comprehension test